Mnemonic Device ‘FRIED’ for the English Teachers of SMP/MTs Muhammadiyah in Banyumas to Teach Recount Paragraphs - Faisal; Bambang Suroso (PT FORMOSA CENDEKIA GLOBAL, 2022)
This community service activity aims to introduce to SMP/MTs Muhammadiyah English teachers in Banyumas Regency a mnemonic device ‘FRIED’ to teach recount paragraphs. It had three primary sessions: a review of recount paragraphs, an explanation of ‘FRIED’ in teaching writing, and peer-teaching practices to utilize the device to write recount paragraphs. The participants deemed that ‘FRIED’ was able to teach the paragraphs and help their students to construct, organize, and develop their recount paragraphs cohesively and coherently. Furthermore, most of them considered that ‘FRIED’ was a suitable device to help their students to improve their oral competency, particularly, in recount genres. They perceived that ‘FRIED’ offers a systematic, appropriate, and creative way to construct, develop and organize the recount paragraph.